2010
DOI: 10.1186/1472-6920-10-51
|View full text |Cite
|
Sign up to set email alerts
|

Learning styles of medical students, general surgery residents, and general surgeons: implications for surgical education

Abstract: Background: Surgical education is evolving under the dual pressures of an enlarging body of knowledge required during residency and mounting work-hour restrictions. Changes in surgical residency training need to be based on available educational models and research to ensure successful training of surgeons. Experiential learning theory, developed by David Kolb, demonstrates the importance of individual learning styles in improving learning. This study helps elucidate the way in which medical students, surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
78
1
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 15 publications
(28 reference statements)
4
78
1
9
Order By: Relevance
“…1 These have been evaluated in the literature by several different disciplines including engineering, pharmacy, nursing, allied health, and others. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Learning style instruments include the Kolb Learning Style Inventory, 18 Honey and Mumford's Learning Style Questionnaire, 19 and the commonly used Myers-Briggs Type Indicator. 20 Of the instruments available, few have been validated or based on sound educational theory.…”
Section: Introductionmentioning
confidence: 99%
“…1 These have been evaluated in the literature by several different disciplines including engineering, pharmacy, nursing, allied health, and others. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Learning style instruments include the Kolb Learning Style Inventory, 18 Honey and Mumford's Learning Style Questionnaire, 19 and the commonly used Myers-Briggs Type Indicator. 20 Of the instruments available, few have been validated or based on sound educational theory.…”
Section: Introductionmentioning
confidence: 99%
“…Ils sont ainsi assez comparables aux étudiants pakistanais étu-diés par Danich et Awan, chez qui prédominait éga-lement le style accommodateur [17] (54,6 %), mais ils se distinguent de ceux de l'étude d'Engels et Gara [18] , qui concluait à une prépondérance du style assimilateur (40 % des étudiants en médecine de l'Université d'Alberta), de ceux de l'étude de Gurpinar et al [19] où le style divergent était prédominant (47,7 % des étudiants de première année d'une université turque) et de ceux de l'étude nord-américaine de Chapman et Calhoun [2] , qui étaient plutôt de style abstrait et actif. Nos étudiants privilégiaient ainsi l'action guidée par l'intuition plutôt que l'analyse logique.…”
Section: Discussionunclassified
“…A previous study has also shown that high achievers approach the teacher to explain parts of the lessons they do not understand. 4 In a study by Engels and de Gara, 5 it was observed that medical students followed the assimilatory learning style of the Kolb learning style inventory. Essentially, people following this learning style enjoyed creating theoretical models and placed importance in theory and logic, and are less interested in people and more concerned with abstract concepts.…”
Section: Discussionmentioning
confidence: 99%